A study of lifelong learning and effect to worker performance - Zuraini , Johari (2014)
Lifelong learning is one of the concepts that can help employee to make improvement of them in working life. These concept also make realized all worker that education is most important to change or improve their performance in organization and also can give effect to others surrounding. The aim of study is to know the effectiveness of lifelong learning and to know it will effect to worker performance or not. The factors that will involved in lifelong learning which is factor of skill, improvement of knowledge and factor of qualification. This study will help employee to involve in continuing education to get more benefit such as can be more proactive and can improve confident level in negotiation during managing the project or business. The other objective is to identify the most dominant factor that will contribute to worker performance. So respondent comprising the student that further studies in Open University Malaysia (OUM) were selected as a samples. The targeted respondent is 66 of people as a samples.The anlysis has been testing by using Pearson correlation to know the relationship between two variables. The result of the analysis show that there are relationship of lifelong learning and effect to worker performance This research done with the regression analysis for hypothesis testing. The researcher would like to suggest some recommendation for further studies to prove that lifelong learning is very important in working life. It include quality of work or confident level in proposed more language in working life. Hopefully that these factor can help in to give effect to worker performance in future